Association of RANKL and EGFR gene expression with bone metastases in patients with metastatic non-small cell lung cancer - Brouns, Anita J.W.M.; Hendriks, Lizza E.L.; Robbesom-van den Berge, Iris J.; Driessen, Annemariek J.H.M.; Roemen, Guido M.J.M.; van Herpen, Britt L.J.; Dekkers, Zoë; Heitzer, Bas; Leunissen, Daphne J.G.; Moonen, Laura; Lunde, Ragnar; Westenend, Marcel; et al. (Frontiers in Oncology, 2023)
Introduction Bone metastases are frequent in patients with non-small cell lung cancer (NSCLC). The receptor activator of Nuclear Factor κB (RANK)/ RANK ligand (RANKL)/osteoprotegerin (OPG) pathway is important in bone metastases development. Furthermore, epidermal growth factor receptor (EGFR) signaling promotes osteoclast formation and stimulation. The understanding of the biological mechanism of bone metastases development might have implications for treatment strategies. Therefore, we studied whether there is an association between EGFR, RANKL, RANK and OPG gene expression in the tumor and presence of bone metastases in patients with NSCLC. Methods From an updated multicenter study, including patients with EGFR mutated (EGFR+), Kirsten rat sarcoma (KRAS+) and EGFR/KRAS wildtype metastatic NSCLC, all patients with available formalin-fixed paraffin-embedded (FFPE) tumor samples were selected. Ribonucleic Acid (RNA) was isolated from these samples and gene expressions of EGFR, RANKL, OPG and RANKL were determined via quantitative Polymerase Chain Reaction (qPCR). Data on demographics, histology and molecular subtyping, sample origin, presence of bone metastasis, SREs and bone progression were collected. Primary endpoint was relation between EGFR, RANK, RANKL, OPG gene expression, RANKL:OPG ratio and bone metastases. Results In 73/335 (32% EGFR+, 49% KRAS+, 19% EGFR/KRAS wildtype) samples from unique patients, gene expression analysis could be performed. Of these 73 patients, 46 (63%) had bone metastases at diagnosis or developed bone metastases during the disease course. No association was found between EGFR expression and presence of bone metastases. Patients with bone metastases had a significantly higher RANKL expression and RANKL:OPG ratio compared to those without. An increased RANKL:OPG ratio resulted in a 1.65x increased risk to develop bone metastases, especially in the first 450 days after diagnosis of metastatic NSCLC. Conclusion Increased RANKL gene expression and RANKL:OPG ratio, but not EGFR expression, was associated with presence of bone metastases. Additionally, an increased RANKL:OPG gene ratio was associated with a higher incidence of bone metastases development.